Modified production line of expanded production of animal feed - Дмитриков, В. П.; Назаренко, О. О.; Запорожець, М. І. (Scientific Progress & Innovations, 2016)
The problems that have developed in the production of grain feed were found. The structure and layout of the flexible production lines for the processing of agricultural raw materials was considered. The factors of influence on the processes of extrusion processing of crop production were analyzed. A modified technology of animal feed production line expanded for various purposes was recommended.